Advances in applied biotechnology. proceedings of the 2nd International Conference on Applied Biotechnology (ICAB 2014) /: proceedings of the 2nd International Conference on Applied Biotechnology (ICAB 2014). Volume I : ([2015]) - Unknown
No abstract available